The Swiss National Registry for Primary Immunodeficiencies: report on the first 6 years' activity from 2008 to 2014. (29th July 2015) - Marschall, K; Hoernes, M; Bitzenhofer-Grüber, M; Jandus, P; Duppenthaler, A; Wuillemin, W A; Rischewski, J; Boyman, O; Heininger, U; Hauser, T; Steiner, U; Posfay-Barbe, K; et al.
Summary: The Swiss National Registry for Primary Immunodeficiency Disorders (PID) was established in 2008, constituting a nationwide network of paediatric and adult departments involved in the care of patients with PID at university medical centres, affiliated teaching hospitals and medical institutions. The registry collects anonymized clinical and genetic information on PID patients and is set up within the framework of the European database for PID, run by the European Society of Immunodeficiency Diseases. To date, a total of 348 patients are registered in Switzerland, indicating an estimated minimal prevalence of 4·2 patients per 100 000 inhabitants. Distribution of different PID categories, age and gender are similar to the European cohort of currently 19 091 registered patients: 'predominantly antibody disorders' are the most common diseases observed ( n = 217/348, 62%), followed by 'phagocytic disorders' ( n = 31/348, 9%). As expected, 'predominantly antibody disorders' are more prevalent in adults than in children (78 versus 31%). Within this category, 'common variable immunodeficiency disorder' (CVID) is the most prevalent PID ( n = 98/217, 45%), followed by 'other hypogammaglobulinaemias' (i.e. a group of non-classified hypogammaglobulinaemias) ( n = 54/217, 25%). Among 'phagocytic disorders', 'chronic granulomatous disease' is the most prevalent PID ( n = 27/31, 87%). The diagnostic delay between onset of symptoms and diagnosis is high, with a median of 6 years for CVID and more than 3 years for 'other hypogammaglobulinaemias'.